Evaluating the Status of Patients Suffering from Diarrhea During the Outbreak Occurred in Shahrekord in 2015 - Moslem Taheri; Seyyed Mohammad Tabatabaei; Mohammadhasan Lotfi; Azimeh Ghaderi; Rashed Jazayeri; Ahmad Reisi (Shahid Sadoughi University of Medical Sciences, 2016)
Introduction: The term diarrheal diseases, a conventional expression and is neither an epidemiological subject nor a class of diseases, because diarrhea is a symptom of many diseases, however, it is defined as the passage of three or more loose or liquid stools per day. Materials and methods: This is a cross-sectional study in which the records of all patients with symptoms of diarrhea encountering health centers during April and May 2015 were used. Results: Females, with a frequency of 56.7 percent, have a larger proportion of clinical symptoms associated with this outbreak. Most of the clinical symptoms related to watery diarrhea (74.5%), fever (62.4%), nausea (61.9%), vomiting (58.2%), and dysentery (24.2%). Most of the food eaten by encountered people with clinical symptoms related to outbreak of diarrhea are the fruits (51.6%), vegetables (42.9%), ice cream (4 %), food outside the home (3.5%), fast food consumption (2.4%). Conclusions:It seems that the possible source of this outbreak is foods such as fruits and vegetables which are abundant in this province at spring and more attention, better management and control on the food is needed according to World Health Day 2015: "from farm to plate, make food safe".